The Skeleton Key - Softley, Iain.; Kruger, Ehren; Hudson, Kate.; Sarsgaard, Peter; Bryant, Joy.; Rowlands, Gena. ([S.l : s.n., 2005)
A hospice nurse working at a spooky New Orleans plantation home finds herself entangled in a mystery involving the house's dark past.
Original release date: 12 Aug 2005.
Director, Iain Softley ; screenplay, Ehren Kruger.
Starring Kate Hudson, Peter Sarsgaard, Joy Bryant, Gena Rowlands.
MPAA rating: PG-13.
Keywords: Feature films; Horror; Mystery; Thriller